English Teachers’ Professional Competence in Utilizing ICT At Madrasah Level : KOMPETENSI PROFESSIONAL GURU BAHASA INGGRIS DALAM MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA JENJANG MADRASAH - Wahyu Nur Azizah; Anugerahwati, Mirjam; Setyowati, Lestari (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
This study investigates at how proficient teachers at using ICT at religiously affiliated school implemented. Discovering out what teachers used in ICT tool and investigating the factors that lie behind their use in educational settings are the purposes of this. Seven state MTs in the Malang district were given a questionnaire to complete as part of the study's qualitative research design. There are twenty-eight English teachers that are available to participate. Presented in the form of descriptive qualitative, this study shows the results that teachers use ICT in their learning with a time preference of once a week. Additional research indicates that instructors' confidence in ICT that will increase their productivity (10.51%) and help them access instructional resources in the classroom (10.38%) are the main reasons why they use it for the learning process. Therefore, it is expected that future studies will continue to examine the ICT proficiency of instructors who are already familiar with its use, as well as how they address any challenges they may have when using it.